Metodologia para análise e ajuste da seletividade de dispositivos de proteção em situações de contingência - Stöhlirck, Leonardo (2018)
The concept of Smart Grid (SG) modified the way of operation and planning of electrical systems, encouraging automation, distributed generation, among others. As a result of this new system design, a series of applications were proposed with a view to optimizing the management of assets both in permanent and in contingency situations. In this sense, this work proposes a methodology for the analysis of the coordination and selectivity of the protection devices in contingency situations, performing the necessary parameterizations in the automated equipment in real time. As a case study, analyzes will be presented in real electrical systems, with the purpose of analyzing the protection system in contingency situations, where they had their topological and electrical characteristics altered. In the case of maneuvers between the electrical networks, the symmetrical and asymmetric short-circuit current values change, as well as the impedance and the power, which can represent a condition of non-coordination and selectivity of the protection equipment, a fact that can propagation of faults and improper actions. The study is based on the distribution network (DN) topology of the Coprel Cooperativa de Energia, which is located in the southern region of Brazil. It is proposed to use the Heuristic method through the Depth Search Strategy to analyze the possibilities of feedback of the loads in the event of a defect, regarding the coordination and selectivity of the protection devices for this new configuration. In this way, the methodology seeks, through a certain failure, to define the new adjustments that can be implemented, if necessary, in order to ensure coordination and selectivity from the new network configuration. With the result, it is expected to guarantee the protection and selectivity of the devices through analysis and calculations of the system in contingency. The new adjustments provided by the calculation will enable fast and secure service to the largest possible number of consumers. The great benefit is related to real-time operation of the system, allowing the parameterization of the protection settings even in emergencies, also guaranteeing the coordination and selectivity of the devices in the system's contingency. The benefits are also compounded by the automatic recomposition of distribution systems in the event of any defect, through automated equipment will automatically calculate the best and fastest way of serving a certain number of consumers.